TfWRKY40 positively regulates diosgenin biosynthesis in Trigonella foenum-graecum L. - Xu, Chuanjia; Tang, Nan; Xu, Yehan; Li, Changfu; Zhang, Yansheng (Frontiers in Plant Science, 2025)
Diosgenin is a bioactive steroidal natural product extraced from plants and serves as an important precursor for the industrial production of steroidal hormone drugs. Despite its pharmacological significance, the biosynthetic and regulatory mechanisms underlying diosgenin production in the medicinal plant T. foenum-graecum remain poorly understood. In this study, we identified TfWRKY40, a WRKY transcription factor from T. foenum-graecum, whose expression strongly correlates with diosgenin accumulation. Using RNA interference and overexpression strategies combined with transcriptomic analysis and targeted metabolite quantification, we demonstrated that silencing of TfWRKY40 led to a 67.60% reduction in diosgenin content, which was accompanied by downregulation of key biosynthetic genes or transcript variants including ACAT1, HMGR1, PMK1, MVD, FPS, SQE2, CAS1, SMO3-1, SMO3-2, 8,7-SI, SMO4-3, CYP90B50, and CYP82J17 in the transgenic hairy roots. Conversely, overexpression of TfWRKY40 resulted in a 59.25% increase in diosgenin levels, along with upregulation of these biosynthetic genes or transcript variants. Taken together, these findings suggest that TfWRKY40 acts as a positive regulator of diosgenin biosynthesis in T. foenum-graecum, likely by activating the transcription of critical pathway genes, particularly CAS1, HMGR1, and CYP90B50. This work highlights TfWRKY40 as a promising target for metabolic engineering strategies aimed at enhancing diosgenin production and facilitating the development of diosgenin-derived steroidal therapeutics.